Prevalence of Non-Communicable Diseases and Access to Healthcare Among Internally Displaced People During the Armed Conflict, Northern State (Sudan) - Elyas HM; Hamid HTA; Arbab AH; Moukhtar OA; Abdelaziz MO (Dove Medical Press, 2024)
Hajer Mohamed Elyas,1 Hind Taj Alser Hamid,2 Ahmed H Arbab,3 Outhman Alsadiq Moukhtar,4 Mohamed Osman Abdelaziz5 1Department of Physiology, Faculty of Medicine, University of Dongola, Dongola, Northern State, Sudan; 2Biomedical Research Laboratory, Faculty of Medicine, University of Dongola, Dongola, Northern State, Sudan; 3Department of Pharmacognosy, Faculty of Pharmacy, University of Khartoum, Khartoum, Khartoum State, Sudan; 4Faculty of Economic and Administrative Sciences, University of Dongola, Dongola, Northern State, Sudan; 5Department of Internal Medicine, Faculty of Medicine, University of Dongola, Dongola, Northern State, SudanCorrespondence: Ahmed H Arbab, Department of Pharmacognosy, Faculty of Pharmacy, University of Khartoum, Al-Qasr Ave, 11111, Khartoum, Sudan, Tel +249 991893200, Email arbabssn@gmail.comBackground: Non-communicable diseases emerge as major public health challenges with increasing prevalence and mortality. The armed conflict in Sudan has resulted in the displacement of 6.8 million people, putting a significant strain on the health sector in the displacement areas. This study aimed to explore the prevalence of non-communicable diseases and access to healthcare services among internally displaced people in Northern Sudan.Methods: A cross-sectional study was conducted among randomly selected internally displaced people in accommodation shelters at Dongola locality. Data were collected by face-to-face interviews using a questionnaire adapted from relevant studies. For data analysis descriptive statistics and chi-square tests were utilized using SPSS-27.Results: 374 participated in the study with a 96.1% response rate. 70% of respondents were 18- 49 years old. 70.9% of respondents were females, and 92.8% of them had no source of financial income. The prevalence of non-communicable diseases was 42.5%, with hypertension (44.7%), diabetes mellitus (24.7%), and thyroid disorders (15.2%) predominating. About 45.7% of patients interrupted their medication, and 38.6% could not access healthcare services, while 57.2% of respondents received free medical care. The study found a statistically significant association between the type of disease and age, gender, residence before displacement, and the Length of displacement.Conclusion: 42.5% of the internally displaced suffer from non-communicable diseases, with hypertension, diabetes mellitus, and thyroid disorders predominating. About 45.3 and 38.6% of them respectively have interrupted their medications and lost regular follow up. The urgent need for improved healthcare services is recommended.Keywords: internally displaced, non-communicable diseases, conflict, Sudan, Northern state